Levofloxacin in veterinary medicine: a literature review. (July 2021) - Sitovs, Andrejs; Sartini, Irene; Giorgi, Mario
Abstract: A potent third-generation antimicrobial fluoroquinolone drug, levofloxacin was introduced into human clinical practice in 1993. Levofloxacin is also used in veterinary medicine, however its use is limited: it is completely banned for veterinary use in the EU, and used extralabel in only companion animals in the USA. Since its introduction to clinical practice, many studies have been published on levofloxacin in animal species, including pharmacokinetic studies, tissue drug depletion, efficacy, and animal microbial isolate susceptibility to levofloxacin. This literature overview highlights the most clinically relevant and scientifically important levofloxacin studies linked to the field of veterinary medicine. Highlights: Published papers on levofloxacin use in veterinary medicine are reviewed. Levofloxacin MIC values of animal microbial isolates are summarized. Levofloxacin pharmacokinetic studies are reviewed.